Generation Z's and Pancasila Democracy: The Impact of Political Parties and Political Leadership - Aleknaek Martua Nababan; Payaman Simanjuntak; Martongo Sitinjak; Risdo Simangunsong (Pancasila: Jurnal Keindonesiaan, 2025)
Generation Z in the current situation is quite interesting to discuss because this age group grew up and developed amid the development of digital and information technology. The entry of Generation Z as civil servant candidates marks a shift in the dynamics of Indonesian government bureaucracy because amid demands that the basic values of Pancasila ideology be strongly instilled along with regulations that bind the civil service. This study answers how perceptions of political parties and political leadership can influence Generation Z to implement Pancasila democracy. This study was designed using a survey and data processed with a quantitative approach using Partial Least Squares - Structural Equation Modeling. This study concludes that perceptions of a political party can have a positive influence on political leadership. Indirectly, this also supports the idea that party ideology will have an impact on the political leadership of future public officials. Thus, perceptions of political leadership among future public officials have a significant influence on how respondents express Pancasila democracy. Thus, this study recommends intensive political education for political parties and their leaders to support the internalization of Pancasila values among public officials and party cadres.